About death at school? Education and teaching majors in the face of humanistic-oriented death education as an element of school education – attitude and selected differentiating factors - Agnieszka Zamarian (Studia z Teorii Wychowania)
The paper deals with the topic of education for the mature reception of the phenomenon of death and its place in school education from the perspective of the conception of Hannelore Wass. It presents the results of research on the attitude of education and teaching majors to humanistic-oriented death educationa as an element of school education and selected factors differentiating it. Data was collected using author’s tool with confirmed, satisfactory psychomeric properties. The conducted analyzes indicates that respondents, depending on their religiosity, personal educational philosphy, experience of contact with a dying person and a chosen field of study, to a greater or lesser extent, recognize the need to implement humanistic-oriented death education in the school environment. These results may become the theoretical basis for projects on making educators and teachers better prepared for executing death education.